Proyecto fotográfico “cuenta hasta diez”: el sentir de una persona ansiosa. - Del Aguila Grondona, Alejandra (2021)
Count till ten is a photographic project that represents the feeling of a person who deals with anxiety. The purpose of the project is to present, to the public, a personal and collective experience of anxiety to generate reflection and conversation on the subject. The photographic series has 21 photographs and one text that go with the images. The theme is relevant since, thanks to the pandemic, cases of mental health have increased. Both, the author's experience and the experiences of others that were collected through interviews, can be seen reflected in the project. Part of the creative process was to include others (who also suffer from anxiety) in order to better communicate to the various audiences.